The Use of Health Information Exchange to Augment Patient Handoff in Long-Term Care: A Systematic Review - Kruse, Clemens Scott; Marquez, Gabriella; Nelson, Daniel; Palomares, Olivia (Applied Clinical Informatics, 2018)
Background Legislation aimed at increasing the use of a health information exchange (HIE) in healthcare has excluded long-term care facilities, resulting in a vulnerable patient population that can benefit from the improvement of communication and reduction of waste.Objective The purpose of this review is to provide a framework for future research by identifying themes in the long-term care information technology sector that could function to enable the adoption and use of HIE mechanisms for patient handoff between long-term care facilities and other levels of care to increase communication between providers, shorten length of stay, reduce 60-day readmissions, and increase patient safety.Methods The authors conducted a systematic search of literature through CINAHL, PubMed, and Discovery Services for Texas A&M University Libraries. Search terms used were (“health information exchange” OR “healthcare information exchange” OR “HIE”) AND (“long term care” OR “long-term care” OR “nursing home” OR “nursing facility” OR “skilled nursing facility” OR “SNF” OR “residential care” OR “assisted living”). Articles were eligible for selection if they were published between 2010 and 2017, published in English, and published in academic journals. All articles were reviewed by all reviewers and literature not relevant to the research objective was excluded.Results Researchers selected and reviewed 22 articles for common themes. Results concluded that the largest facilitator and barrier to the adoption of HIE mechanisms is workflow integration/augmentation and the organizational structure/culture, respectively. Other identified facilitator themes were enhanced communication, increased effectiveness of care, and patient safety. The additional barriers were missing/incomplete data, inefficiency, and market conditions.Conclusion The long-term care industry has been left out of incentives from which the industry could have benefited tremendously. Organizations that are not utilizing health information technology mechanisms, such as electronic health records and HIEs, are at a disadvantage as insurers switch to capitated forms of payment that rely on reduced waste to generate a profit.
Keywords: health information exchanges; clinical data; older patients; information technology; communications